Implementasi Metode Design Thinking Pada Perancangan UI/UX Design Aplikasi Dagang.in - Cahya Sonny Surachman; Muhammad Riyan Andriyanto; Catur Rahmawati; Pristi Sukmasetya (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
The spread of Corona Virus Disease 2019 (COVID) is very disturbing for MSMEs, especially micro MSMEs. In this case, itinerant traders need convenience in trading during the pandemic because the government has imposed several policies to deal with COVID-19. The policy implemented was emergency PPKM which resulted in road access in several areas being closed. According to the Kemenkop MSMEs, it is estimated that 37,000 MSMEs will provide reports on the impact felt by the implementation of the new policy. Therefore, this application is designed by providing solutions as a form to make trading easier and increase Indonesia's economic growth. In this design using the design thinking method which consists of empathize, define, ideate, prototype, and test stages. After the development, finally got the results to create a mobile application model with the name